Circulating endostatin as a risk factor for cardiovascular events in patients with stable coronary heart disease: A CLARICOR trial sub-study. (May 2019) - Ruge, Toralph; Carlsson, Axel C.; Kjøller, Erik; Hilden, Jørgen; Kolmos, Hans Jørn; Sajadieh, Ahmad; Kastrup, Jens; Jensen, Gorm Boje; Larsson, Anders; Nowak, Christoph; Jakobsen, Janus Christian; Winkel, Per; et al.
Abstract: Background and aims: Raised levels of serum endostatin, a biologically active fragment of collagen XVIII, have been observed in patients with ischemic heart disease but association with incident cardiovascular events in patients with stable coronary heart disease is uncertain. Methods: The CLARICOR-trial is a randomized, placebo-controlled trial of stable coronary heart disease patients evaluating 14-day treatment with clarithromycin. The primary outcome was a composite of acute myocardial infarction, unstable angina pectoris, cerebrovascular disease or all-cause mortality. In the present sub-study using 10-year follow-up data, we investigated associations between serum endostatin at entry (randomization) and the composite outcome and its components during follow-up. The placebo group was used as discovery sample (1204 events, n = 1998) and the clarithromycin-treated group as replication sample (1220 events, n = 1979). Results: In Cox regression models adjusting for cardiovascular risk factors, glomerular filtration rate, and current pharmacological treatment, higher serum endostatin was associated with an increased risk of the composite outcome in the discovery sample (hazard ratio per standard deviation increase 1.11, 95% CI 1.03–1.19, p = 0.004), but slightly weaker and not statistically significant in the replication sample (hazard ratio 1.06, 95% CI 1.00–1.14, p = 0.06). In contrast, strong and consistent associations were found between endostatin and cardiovascular and all-cause mortality in all multivariable models and sub-samples. Addition of endostatin to a model with established cardiovascular risk factors provided no substantial improvement of risk prediction (<1%). Conclusions: Raised levels of serum endostatin might be associated with cardiovascular events in patients with stable coronary heart disease. The clinical utility of endostatin measurements remains to be established. Graphical abstract: Image 1 Highlights: Higher serum endostatin was associated with higher risk of the composite cardiovascular outcome in the discovery sample. Slightly weaker associations were seen in the replication sample ( p =0.06). In contrast, serum endostatin predicted cardiovascular and all-cause mortality in all multivariable models and sub-samples. Endostatin might be involved in the development of cardiovascular events in patients with stable coronary heart disease.